The Impact of Phonetic Context on Meaning Interpretation in the Collection of Books and Letters by Imam Zaid bin Ali (PBUH) - Yusuf Taha, Researcher. Wasan; Ali Hussein Mahdi, Prof. Dr. Hussein (Basra studies journal, 2025)
Meaning is the ultimate goal for the recipient, sought within texts, symbols, or discourse. Linguistic studies have explored this pursuit, investigating methods for uncovering meaning. Some approaches provide direct access with ease, while others require the recipient to reflect deeply to discern precise meaning. Contextual theory plays a key role in navigating this path and resolving issues of ambiguous or overlapping meanings. One such context is the phonetic context, which significantly influences the revelation of meaning. This research aims to explore the phonetic context within a clear and eloquent Arabic text, rich in the arts of Arabic expression: The Collection of Books and Letters of Imam Zaid bin Ali (PBUH). Through the analysis of these noble texts, the study examines prominent phonetic phenomena and their contribution to uncovering or defining the meanings intended by Imam Zaid. The phonetic context is a vital element of the broader linguistic context, working in tandem with other linguistic and non-linguistic contexts to determine meaning. The phonetic context holds considerable influence, a fact recognized by ancient Arab linguists, whose works demonstrate a keen sensitivity to sounds and their meanings. Modern linguists have also highlighted this relationship between sound and meaning, noting that sounds often mirror nature. Even when a sound does not directly convey meaning, it can evoke an intuitive sense or emotional readiness to accept the intended meaning.